Enhanced Caspase Activity Contributes to Aortic Wall Remodeling and Early Aneurysm Development in a Murine Model of Marfan Syndrome. Issue 1 (January 2015) - Emrich, Fabian C.; Okamura, Homare; Dalal, Alex R.; Penov, Kiril; Merk, Denis R.; Raaz, Uwe; Hennigs, Jan K.; Chin, Jocelyn T.; Miller, Miquell O.; Pedroza, Albert J.; Craig, Juliana K.; Koyano, Tiffany K.; et al.
Abstract : Objective—: Rupture and dissection of aortic root aneurysms remain the leading causes of death in patients with the Marfan syndrome, a hereditary connective tissue disorder that affects 1 in 5000 individuals worldwide. In the present study, we use a Marfan mouse model ( Fbn1 C1039G/+ ) to investigate the biological importance of apoptosis during aneurysm development in Marfan syndrome. Approach and Results—: Using in vivo single-photon emission computed tomographic-imaging and ex vivo autoradiography for Tc99m-annexin, we discovered increased apoptosis in the Fbn1 C1039G/+ ascending aorta during early aneurysm development peaking at 4 weeks. Immunofluorescence colocalization studies identified smooth muscle cells (SMCs) as the apoptotic cell population. As biological proof of concept that early aortic wall apoptosis plays a role in aneurysm development in Marfan syndrome, Fbn1 C1039G/+ mice were treated daily from 2 to 6 weeks with either (1) a pan-caspase inhibitor, Q-VD-OPh (20 mg/kg), or (2) vehicle control intraperitoneally. Q-VD-OPh treatment led to a significant reduction in aneurysm size and decreased extracellular matrix degradation in the aortic wall compared with control mice. In vitro studies using Fbn1 C1039G/+ ascending SMCs showed that apoptotic SMCs have increased elastolytic potential compared with viable cells, mostly because of caspase activity. Moreover, in vitro (1) cell membrane isolation, (2) immunofluorescence staining, and (3) scanning electron microscopy studies illustrate that caspases are expressed on the exterior cell surface of apoptotic SMCs. Conclusions—: Caspase inhibition attenuates aneurysm development in an Fbn1 C1039G/+ Marfan mouse model. Mechanistically, during apoptosis, caspases are expressed on the cell surface of SMCs and likely contribute to elastin degradation and aneurysm development in Marfan syndrome. Abstract : Supplemental Digital Content is available in the text.